Activation of Adenosine Monophosphate-Activated Protein Kinase Drives the Aerobic Glycolysis in Hippocampus for Delaying Cognitive Decline Following Electroacupuncture Treatment in APP/PS1 Mice - Li, Jianhong; Zhang, Bingxue; Jia, Weiwei; Yang, Minguang; Zhang, Yuhao; Zhang, Jiayong; Li, Le; Jin, Tingting; Wang, Zhifu; Tao, Jing; Chen, Lidian; Liang, Shengxiang; et al. (Frontiers in Cellular Neuroscience, 2021)
Aerobic glycolysis (AG), an important pathway of glucose metabolism, is dramatically declined in Alzheimer's disease (AD). AMP-activated protein kinase (AMPK) is a key regulator to maintain the stability of energy metabolism by promoting the process of aerobic glycolysis and regulate glucose metabolism. Interestingly, it has been previously reported that electro-acupuncture (EA) treatment can improve cognitive function in Alzheimer's disease through the enhancement of glucose metabolism. In this study, we generated AMPK-knockdown mice to confirm the EA effect on AMPK activation and further clarify the mechanism of EA in regulating energy metabolism and improving cognitive function in APP/PS1 mice. The behavioral results showed that EA treatment can improve the learning and memory abilities in APP/PS1 mice. At the same time, the glucose metabolism in hippocampus was increased detected by MRI-chemical exchange saturation transfer (MRI-CEST). The expression of proteins associated with aerobic glycolysis in hippocampus were increased simultaneously, including HK2, PFKFB3 and PKM2. Moreover, the knockdown of AMPK attenuated aerobic glycolysis activated by EA treatment. In conclusion, this study proved that electro-acupuncture can activate AMPK to enhance the process of aerobic glycolysis in early stage of Alzheimer's disease.